Paradoks Kebijakan Pembangunan Perumahan Mewah dan Perumahan Kumuh - Ahmad Arfandi Musida; Subaidi (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
This study aims to show the paradox of housing development in urban areas. This study uses a literature review method. The results of the study show that housing development in urban areas experiences a paradox on the one hand, building houses for those who do not need a house as a place to live but as an investment. However, displacing homeless people who need a place to live. The policy alternatives offered are: (1) building a political contract as an effort to eradicate policies that pay attention to housing policies; (2) a win-win policy solution in addition to paying attention to good city planning also provides a solution for those who are homeless so that they still have a place to live that is not far from where they work